Femoral neck fractures after hip resurfacing. - Steffen, RT; Foguet, P; Krikler, S; Gundle, R; Beard, D; Murray, D (2009)
Femoral neck fracture is an important early complication after hip resurfacing. Our aims were firstly to determine the incidence of fracture in an independent series and secondly, in a case control study, to investigate potential risk factors. Fifteen femoral neck fractures occurred in a series of 842 procedures, representing an incidence of 1.8%. No relationship existed between age, sex, and fracture incidence. Mechanical factors such as notching, femoral neck lengthening, and varus alignment of the femoral component were found to have a similar incidence in both fracture and control groups. The proportion of patients that had at least 1 mechanical risk factor was not different between the 2 groups (fracture group, 50%; control group, 41%). Established avascular necrosis of the femoral head was evident in all retrieved femoral heads (n = 9) of patients who sustained postoperative fracture; in none of these patients was avascular necrosis the initial diagnosis. This study suggests that in our practice, mechanical factors, such as neck notching, neck lengthening, or varus angulations, are not the primary cause of femoral neck fractures.